AS AUDIÊNCIAS DE CUSTÓDIA E AS PESSOAS COM TRANSTORNO MENTAL EM CONFLITO COM A LEI - Campos, Bruno da Silva (2022)
This study aims to analyze the effects of the medicalization of madness on decisions handed down in custody hearings before people with mental disorders in conflict with the law. For this, we describe the itinerary of these people who enter the criminal justice system through the custody hearing and how the interlocution health and justice in Espírito Santo has been approached, having Collective Health as a theoretical basis. Under methodological aspects, it is a work of qualitative design, consisting of the following steps for data production: documental analysis, and in-depth interviews. The results are presented in the form of articles and, based on them, we aim to contribute to the discussion, referrals and procedures concerning people with mental disorders who commit crimes. As well as providing subsidies for the implementation and strengthening of public policies that concern this portion of the population and that enhance the mental health network and, consequently, living in the city, leaving behind the asylum, institutional and prison model.